The Auxiliary equation is given by,
"[(m-1)^2(m+1)^2]=0"
The roots of the above equation are,
1,1,-1,-1
Therefore The complimentary function,
C.F.="(c_1+c_2x)e^x+(c_3+c_4x)e^{-x}" ......(1)
Particular Integral, P.I.= "\\frac{sin^2x}{2(D^2-1)^2}+\\frac{e^x}{(D^2-1)^2}"
= "\\frac{sin^2x}{2(-1-1)^2}+\\frac{xe^x}{2(D^2-1)\\times 2D}"
="\\frac{sin^2x}{2(-2)^2}+\\frac{x^2e^x}{4(3D^2-1)}"
="\\frac{sin^2x}{8}+\\frac{e^x}{4(3.1-1)}"
="\\frac{sin^2x}{8}+\\frac{e^x}{8}"
So complete solution=C.F+P.I.
y ="(c_1+c_2x)e^x+(c_3+c_4x)e^{-x}+\\frac{sin^2x+e^x}{8}"
Comments
Leave a comment